Pengaruh Bahan Ajar Lap Book Terhadap Pembelajaran Matematika Kelas 1 SD Muhammadiyah 07 Medan Denai - Aswara, Indah Anggreini Try (Journal of Sustainable Education, 2025)
This study aims to determine the effect of using lapbook learning materials on student learning outcomes in Mathematics subjects of grade 1 of Muhammadiyah 07 Elementary School Medan Denai. The method used is quantitative with a pre-experimental design approach, especially the one group pre-test and post-test model. The research sample consisted of 13 students. The research instrument was a pretest and posttest to measure learning outcomes before and after treatment. The results showed that the average posttest score (88.92) was higher than the pretest (78.61), and all students achieved the Minimum Completion Criteria (KKM) after using lapbook media. The average difference in learning outcomes of 10.31 points indicates a significant effect of using lapbook learning materials on improving students' Mathematics learning outcomes. Thus, lapbook media is effectively applied in Mathematics learning for grade 1 to improve student understanding and participation